What is Outcome Harvesting? - and Wilson-Grau, Ricardo (2014)
Ricardo Wilson-Grau, former Chair of the Board of Stewards of the Outcome Mapping Learning Community, introduces Outcome Harvesting, an approach for retrospective identification of outcomes based on the principles of Outcome Mapping. More details here: http://www.outcomemapping.ca/nuggets/outcome-harvesting